DETERMINATION OF THE EFFICIENCY AND EFFICACY OF BIO-CHEMICAL FERTILIZER ON THE SOIL, YIELD AND GROWTH PERFORMANCE OF BLACK PEPPER (Piper nigrum L.) - Ann, Yap Chin (JOURNAL OF ADVANCES IN AGRICULTURE, 2015)
The last nutrient management review of black pepper was done in 1968. There is, therefore, a need to develop new technology to improve pepper production and transfer that technology to production site. This experiment was carried out to study the effect of newly developed biochemical fertilizer on some physiological characteristics, yield and soil fertility of pepper. The treatment consisted of T1 (BS): chemical fertilizer (N:12%, P:12%, K:17%); T2 (BK1): biochemical fertilizer F1 N:15%, P:5%, K:14) and T3 (BK2): biochemical fertilizer F2 (N:13%, P:4%, K:12). The biochemical fertilizer F1 out-yielded chemical and biochemical fertilizer F2 by 75.38% and 16.45% respectively with the higher yield being associated with various phonotypical alterations, which are reported here. Significant measureable changes were observed in physiological processes and plant characteristics, such as large leaf area index, more chlorophyll content and high photosynthesis rate coupled with lower transpiration rate in biochemical fertilizer F1(BK1) treatment compared with other treatment. The high fertility level in biochemical fertilizer F1 and biochemical fertilizer F2 (BK2) reflected the important of organic material in improving soil quality. In conclusion, the achieve high growth performance and yield in pepper, chemical fertilizer alone is insufficient whilst combination of organic and inorganic fertilizer with balance nutrient content gave a significant increase in yield and growth of pepper.